Multidisciplinary Analysis and Medicolegal Approach of the Incest - Meke, Muhammed Said; Dokgöz, Halis; Bilgin, Nursel Gamsız; Kar, Hakan (The Bulletin of Legal Medicine, 2024)
Objective: The aim of this study was to evaluate and discuss the sociodemographic characteristics and possible risk factors of incest cases which are discussed in a broad scope regardless of blood relatives, referred to the forensic medicine outpatient clinic with a multidisciplinary approach. Methods: Between 01.01.2010 and 31.12.2020, data obtained from genital examination reports, consultations and test results of 288 incest cases who applied were retrospectively analyzed. Results: It has been found that, 86.5% of the cases were children with a mean age of 11.6 years (±3.936), 47.2% (n=136) of the perpetrators were first and second degree relatives, and the most common ones were, father, brother and stepfather. The mean age of the perpetrators was 29.8 years (±13.32) and they were married males with low educational and socioeconomic status. Incest was not reported for a long time, was usually accompanied by violence and occurred indoors, often in the home of the victim and the perpetrator. Vaginal and anal penetration were the most frequently alleged types of abuse and 73.5% (n=155) of the cases had a psychopathology, most commonly post-traumatic stress disorder and major depressive disorder. Conclusion: In order to reveal incest, awareness should be raised through trainings in fields such as education, health and social services and the public should be informed about incest. The importance of multidisciplinary approach in revealing incest should be emphasized.